Inflammation Theories in Psychotic Disorders: A Critical Review - Suvisaari, Jaana; Mantere, Outi (Infectious Disorders - Drug Targets, 2013)
Recent research suggests that inflammation and immunity may have a role in the etiology of psychotic disorders. There is evidence of proinflammatory activation of the innate immune system and an activation of the T-cells of the adaptive immune system in both schizophrenia and bipolar disorder. Studies of antipsychotic-naive patients with firstepisode psychosis have found that inflammation is present already at this stage. Some of these abnormalities resolve after the initiation of treatment, suggesting that they are state markers of acute psychosis, but other abnormalities persist. There is also evidence for prenatal infections being involved in the etiology of schizophrenia. Several hypotheses link inflammation and immunity with psychotic disorders. In this review, we focus on hypotheses related to prenatal development, disturbed regulation of neurogenesis, microglial activation, autoimmunity and microbial environment, and consider the potential confounding effects related to stress, childhood adversities, lifestyle and medical comorbidity as well as some methodological limitations. We also review the current evidence for the effectiveness of anti-inflammatory medication in the treatment of psychotic disorders.
Keywords: psychotic disorders